INFLUENCE OF Immersion Time Tofu IN SALT SOLUTION ON FORMALINE RESIDUE: INFLUENCE OF Immersion Time Tofu IN SALT SOLUTION ON FORMALINE RESIDUE (Journal of Health, Technology and Science (JHTS), 2023)
Tofu is a food ingredient made from soybeans and contains a lot of nutritional value, so there are traders who use formalin as a preservative. Formalin is an efficient chemical additive, but is prohibited from being added to food (food). This study aims to determine the presence of formalin residues in tofu based on variations in salt solution soaking time.The research method used is experimental. Data obtained from the Test Kit Formaldehyda with two treatments based on the addition of formalin and salt solution. The treatments were: 1. P1 (6% formalin) and 2. P2 (6% salt solution).The results showed that from 32 samples of tofu soaked in salt solution 45 minutes, 60 minutes, 75 minutes and 90 minutes were tested using reagents A1 1 ml and A2 3 ml. It shows a decrease in formalin residue as much as 45.63%, 69.28%, 82.36% and 91.80%.
Keywords: Soaking Time Tofu, Salt Solution, and Residue Formalin